Think Pair Share Method: Upaya Meningkatkan Motivasi dan Hasil Belajar pada Pelajaran Matematika Materi Sistem Persamaan Linear Dua Variabel di MTs Negeri 1 Yogyakarta - Anik Lestari (Jurnal Pendidikan Madrasah, 2020)
This research aims to describe the results of mathematics learning by using the think pair share method and increase the motivation to learn students of class VIII-F MTs Negeri 1 Yogyakarta school year 2018/2019. The observed motivation includes five aspects, namely the commitment to the task, persistence in learning, diligent in the face of difficulties, can answer his opinion and be interested in various problems. This research using class action methods (PTK) is carried out in two cycles. The results of the study show that: (1) Student motivation for Learning mathematics in cycle I from 32 students, 12.50% reaching high category, increased to 43.75% in cycle II; (2) The increase in student learning results is demonstrated by the increasing average of student learning outcomes at Cycle I, 50.00% has been completed with the average value of 72.23, increasing to 78.10% in cycle II by an average of 76.79. The think pair share method can be applied in math learning process.